Evaluation of Enamel Surface after Removal of Adhesive Resin: An in Vitro Study - Pyakurel, Geeta; Hassan, Gazi Shamim; Sajedeen, Mahmood (Orthodontic Journal of Nepal, 2018)
Introduction: Preservation of the enamel surface during the removal of orthodontic appliance is an essential aspect for clinicians. However, various therapeutic measures can affect the enamel surface. The objective of the research is to evaluate the roughness of enamel surface after the removal of adhesive resin. Materials & Method: 40 extracted human premolar teeth were randomly divided into two groups and the enamel surfaces were initially subjected to profilometer for the assessment of surface roughness. Following bracket bonding, debonding was done and adhesive resin was removed by stainless steel bur in Group A and tungsten carbide bur in Group B. Again, the surface roughness was measured by profilometer. Independent t-test was performed to compare the enamel surface roughness between two groups and paired t-test to compare the enamel surface roughness within the groups. Result: The mean average surface roughness of stainless steel bur was 27.009 ± 4.8420 μm and tungsten carbide was 31.426 ± 5.0956 μm. The result showed that there was significant difference in enamel surface roughness between two groups. Conclusion: The roughness values were found to be significantly decreased with the use of stainless steel bur (SS) than tungsten carbide bur (TC).